HV pulse modulator with switch on HV IGBT transistor - Dolgov, A.; Kildisheva, O. (Вопросы атомной науки и техники, 2004)
The new generation modulator with a solid-state switch to provide the plate pulse supply of RF generators of hydrogen-ion linear accelerators is described. The use of a solid-state switch, instead of a vacuum tube, allowed to increase the efficiency and reduce the modulator overall dimensions due to eliminating the auxiliary power supplies for the vacuum tube and to use a comparatively low charging voltage level.